Natural History of Keloids: A Sociodemographic Analysis Using Structured and Unstructured Data - Anna Swenson; Jessica K. Paulus; Yoojin Jung; Stefan Weiss; Brian Berman; Elena Peeva; Yuji Yamaguchi; Prethibha George; Oladayo Jagun (Adis, Springer Healthcare, 2023)
Abstract Introduction Keloids are lesions characterized by the growth of dense fibrous tissue extending beyond original wound boundaries. Research into the natural history of keloids and potential differences by sociodemographic factors in the USA is limited. This real-world, retrospective cohort study aimed to characterize a population of patients with keloids compared with matched dermatology and general cohorts. Methods Patients with ≥ 2 International Classification of Diseases codes for keloid ≥ 30 days apart and a confirmed keloid diagnosis from clinical notes enrolled in the OM1 Real-World Data Cloud between 1 January 2013 and 18 March 2022 were age- and sex-matched 1:1:1 to patients without keloids who visited dermatologists ("dermatology cohort") and those who did not ("general cohort"). Results are presented using descriptive statistics and analysis stratified by cohort, race, ethnicity, household income, and education. Results Overall, 24,453 patients with keloids were matched to 23,936 dermatology and 24,088 general patients. A numerically higher proportion of patients with keloids were Asian or Black. Among available data for patients with keloids, 67.7% had 1 keloid lesion, and 68.3% had keloids sized 0.5 to < 3 cm. Black patients tended to have larger keloids. Asian and Black patients more frequently had > 1 keloid than did white patients (30.6% vs. 32.5% vs. 20.5%). Among all patients with keloids who had available data, 56.4% had major keloid severity, with major severity more frequent in Black patients. Progression was not significantly associated with race, ethnicity, income, or education level; 29%, 25%, and 20% of the dermatology, keloid, and general cohorts were in the highest income bracket (≥ US$75,000). The proportion of patients with income below the federal poverty line (< US$22,000) and patterns of education level were similar across cohorts. Conclusion A large population of patients in the USA with keloids was identified and characterized using structured/unstructured sources. A numerically higher proportion of patients with keloids were non-white; Black patients had larger, more severe keloids at diagnosis.